Arylfurans as potential Trypanosoma cruzi trypanothione reductase inhibitors - Renata B de Oliveira; Aline BM Vaz; Rosana O Alves; Daniel B Liarte; Claudio L Donnici; Alvaro J Romanha; Carlos L Zani (Memorias do Instituto Oswaldo Cruz, 2006)
The natural lignans veraguensin and grandisin have been reported to be active against Trypanosoma cruzi bloodstream forms. Aiming at the total synthesis of these and related compounds, we prepared three 2-arylfurans and eight 2,5-diarylfurans. They were evaluated for their potential as T. cruzi trypanothione reductase (TR) inhibitors as well against the parasite's intracellular (amastigote) and bloodstream (trypomastigote) forms. Compound 12 was the most effective against TR with an IC50 of 48.5 µM while 7 and 14 were active against amastigotes, inhibiting the parasite development by 60% at 20 µg/ml (59 and 90 µM, respectively). On the other hand, none of the compounds was significantly active against the parasite bloodstream forms even at 250 µg/ml (0.6-1.5 mM).